Examining the core competencies for success in the hotel industry: The case of Cyprus - Marneros, Stelios; Papageorgiou, George; Efstathiades, Andreas (My University, 2021)
This paper investigates the necessary core competencies for a successful career in the hotel industry. For this purpose, two survey questionnaire instruments were administered to collect data based on the views of both educators and hospitality professionals in Cyprus. Utilizing the exploratory factor analysis technique six-core competency factors were identified: Leadership and Critical Thinking, Information Technology and Financial Analysis, Human Relations -Communication, Interpersonal Communication-Cultural Diversity, Human Resource Management and Professional Image-Operational Knowledge. Consequently, a model emerged for identifying and developing core competencies required by the hotel industry that is useful for educators, as well as hotel industry professionals.
Keywords: Hospitality education; Hotel industry; Hospitality management; Core competencies; Competency model